Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1037/edu0000278
|View full text |Cite
|
Sign up to set email alerts
|

Learning vocabulary from educational media: The role of pedagogical supports for low-income preschoolers.

Abstract: This article reports on two studies designed to examine the landscape of online streamed videos, and the features that may support vocabulary learning for low-income preschoolers. In Study 1, we report on a content analysis of 100 top language-and literacy-focused educational media programs streamed from five streaming platforms. Randomly selecting two episodes from each program, we identified the prevalence of vocabulary opportunities, and the pedagogical supports-techniques or features in these media that ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 62 publications
1
26
0
2
Order By: Relevance
“…Rather, we would argue that the pause allowed the time and encouraged the effort to make predictions when it occurred before the monster names, and it was the effort to predict and how that effort may have heightened children’s attention that made the new names that followed a pause more memorable. In a recent review of educational media supports for teaching vocabulary, Neuman, Wong, Flynn, and Kaefer (2019) categorized the use of a pause before the introduction of a target vocabulary item as an attention-directing cue. Rice et al (1992) also suggested that pauses before novel words could be potentially helpful for making words easier to segment from the stream of speech.…”
Section: Discussionmentioning
confidence: 99%
“…Rather, we would argue that the pause allowed the time and encouraged the effort to make predictions when it occurred before the monster names, and it was the effort to predict and how that effort may have heightened children’s attention that made the new names that followed a pause more memorable. In a recent review of educational media supports for teaching vocabulary, Neuman, Wong, Flynn, and Kaefer (2019) categorized the use of a pause before the introduction of a target vocabulary item as an attention-directing cue. Rice et al (1992) also suggested that pauses before novel words could be potentially helpful for making words easier to segment from the stream of speech.…”
Section: Discussionmentioning
confidence: 99%
“…Parasocial interaction is used to elicit small talk to build rapport and educational replies to foster learning. Preschool children who respond to television prompts learn more of the targeted lessons (Anderson et al, ), understand the program plot better (Calvert, Strong, Jacobs, & Conger, ), and master more vocabulary (Neuman, Wong, Flynn, & Kaefer, ). A limitation of this approach is that the child can say anything to a character in a television program, whether it be correct or incorrect, on‐topic or off‐topic, and the character will continue as if they heard a meaningful reply, whether the child made one or not (Roseberry et al, ).…”
Section: Social Meaningfulness Parasocial Relationships and Learningmentioning
confidence: 99%
“…They additionally promoted attention to the appropriate portions of the screen when providing word labels or naming pictured examples. Prior research suggests that cues within media that direct attention to relevant parts of the screen and provide repetition of vocabulary are particularly beneficial to vocabulary learning from educational media (Neuman, Wong, Flynn, & Kaefer, 2019). Coviewers were able to enhance the learning environment by including repetition and visual attention-directing elements through pointing and vocalizations indicating interest.…”
Section: Our Coviewing Enactmentmentioning
confidence: 99%
“…showing that those with stronger vocabularies are able to learn new words more easily (e.g., Blewitt et al, 2009;Neuman et al, 2019). As such, it seems that the same exposure to educational media for children with higher and lower baseline vocabularies is likely to exacerbate rather than ameliorate the gap in vocabularies between these groups.…”
mentioning
confidence: 99%